Cardiac dose from tangential breast cancer radiotherapy in the year 2006. - Taylor, C; Povall, J; McGale, P; Nisbet, A; Dodwell, D; Smith, J; Darby, S (2008)
PURPOSE: To quantify the radiation doses received by the heart and coronary arteries from contemporary tangential breast or chest wall radiotherapy. METHODS AND MATERIALS: Fifty consecutive patients with left-sided breast cancer and 5 consecutive patients with right-sided breast cancer treated at a large United Kingdom radiotherapy center during the year 2006 were selected. All patients were irradiated with 6- or 8-MV tangential beams to the breast or chest wall. For each dose plan, dose-volume histograms for the heart and left anterior descending (LAD) coronary artery were calculated. For 5 of the left-sided and all 5 right-sided patients, dose-volume histograms for the right and circumflex coronary arteries were also calculated. Detailed spatial assessment of dose to the LAD coronary artery was performed for 3 left-sided patients. RESULTS: For the 50 patients given left-sided irradiation, the average mean (SD) dose was 2.3 (0.7) Gy to the heart and 7.6 (4.5) Gy to the LAD coronary artery, with the distal LAD receiving the highest doses. The right and circumflex coronary arteries received approximately 2 Gy mean dose. Part of the heart received >20 Gy in 22 left-sided patients (44%). For the 5 patients given right-sided irradiation, average mean doses to all cardiac structures were in the range 1.2 to 2 Gy. CONCLUSIONS: Heart dose from left-tangential radiotherapy has decreased considerably over the past 40 years, but part of the heart still receives >20 Gy for approximately half of left-sided patients. Cardiac dose for right-sided patients was generally from scattered irradiation alone.